2015
DOI: 10.11646/zootaxa.3963.1.3
|View full text |Cite
|
Sign up to set email alerts
|

An additional record of Kyphosus vaigiensis (Quoy & Gaimard, 1825) (Osteichthyes, Kyphosidae) from Sicily clarifies the confused situation of the Mediterranean kyphosids

Abstract: The lowfin chub, Kyphosus vaigiensis, is reported for the first time off Favignana Island, Sicily, central Mediterranean Sea. The specimen was identified on the basis of morphometric and meristic characters as well as mitochondrial DNA sequences (COI and 16S-rDNA). Two, perhaps three, Kyphosus species-K. bigibbus, K. sectatrix and K. vaigiensis-have been occasionally recorded in the Mediterranean. These species occur both in the Atlantic and Indo-Pacific regions but it is likely they entered the Mediterranean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In fact, this sequence is now reassigned as K. sectatrix in the BOLD database. Two K. sectatrix sequences (BAHA219-08 and MFSP413-10) mentioned in the study by Mannino et al (2015) shared the same haplotype found in the present study with another 12 sequences identified as K. bigibbus (BIN:AAF3652).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In fact, this sequence is now reassigned as K. sectatrix in the BOLD database. Two K. sectatrix sequences (BAHA219-08 and MFSP413-10) mentioned in the study by Mannino et al (2015) shared the same haplotype found in the present study with another 12 sequences identified as K. bigibbus (BIN:AAF3652).…”
Section: Discussionsupporting
confidence: 84%
“…As occurred with other warm-water affinity fishes found in Galician waters, K. vaigiensis was previously recorded in the Mediterranean Sea, where it was reported under the synonym, K. incisor (Azzurro et al 2013), a misidentification of K. sectatrix (Ligas et al 2011) finally clarified by Knudsen and Clements (2013), or with its current name (Mannino et al 2015). This seems to confirm a general and gradual northward displacement of these species in the eastern Atlantic, using the Gibraltar Strait as an escape valve in this migration to the north.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Whether the introduction path to the Mediterranean Sea is the Suez Canal or the Straits of Gibraltar is still unclear (Mannino et al, 2015), but given that the species' juveniles are usually pelagic and are found associated with floating objects (Knudsen & Clements, 2016), its introduction should possibly be attributed to natural range expansion rather than dispersal due to human activities (Zenetos et al, 2012).…”
Section: N Michailidis and M Rousoumentioning
confidence: 99%